Development of the WHO eye care competency framework - Mitasha Yu; Stuart Keel; Silvio Mariotti; Jody-Anne Mills; Andreas Müller (BMC, 2023)
Abstract Background The eye care workforce, particularly in lower resource settings, face challenges of limited integration into the health system, limited workforce capacity, mismatch of workforce to population need and poor quality of care. In recognition of these challenges, coupled with a gap in existing tools, provides a strong rationale for the development of the Eye care competency framework (ECCF). Methods A mixed methods approach was utilised to develop and validate the ECCF. Content was developed by extracting relevant components of existing frameworks used both within and outside of eye care. A diverse technical working group provided feedback and guidance on the structure, design, and content to create a preliminary draft. Competencies and activities were validated using a modified-Delphi study, and the framework was then piloted at four sites to understand how the tool can be implemented in different settings. Results The final version of the ECCF included eight outcomes, nine guiding principles, and content of each of the key elements, including the six domains, 22 competencies, 21 activities, 193 behaviours and 234 tasks, and the knowledge and skills that underpin them. 95/112 participants from the six WHO regions completed the modified-Delphi study, yielding an average of 96% agreement across the competencies and activities in the ECCF. The pilot showcased the versatility and flexibility of the ECCF, where each of the four sites had a different experience in implementing the ECCF. All sites found that the ECCF enabled them to identify gaps within their current workforce documentation. Conclusions The ECCF was developed using a collaborative approach, reflecting the opinions of participants and stakeholders from all around the world. The comprehensive competencies and activities developed in the ECCF encompass the diverse roles of eye care workers, and thus encourage multi-disciplinary care and better integration into the health system. It is recommended that eye care workforce planners and developers use the ECCF, and adapt it to their context, to support workforce development and focus on the quality and scope of eye care service provision.